Changes in microbial communities and associated water and gas geochemistry across a sulfate gradient in coal beds: Powder River Basin, USA. (15th January 2019) - Schweitzer, Hannah; Ritter, Daniel; McIntosh, Jennifer; Barnhart, Elliott; Cunningham, Al B.; Vinson, David; Orem, William; Fields, Matthew W.
Abstract: Competition between microbial sulfate reduction and methanogenesis drives cycling of fossil carbon and generation of CH4 in sedimentary basins. However, little is understood about the fundamental relationship between subsurface aqueous geochemistry and microbiology that drives these processes. Here we relate elemental and isotopic geochemistry of coal-associated water and gas to the microbial community composition from wells in two different coal beds across CH4 and SO4 2− gradients (Powder River Basin, Montana, USA). Areas with high CH4 concentrations generally have higher alkalinity and δ 13 C-DIC values, little to no SO4 2−, and greater conversion of coal-biodegradable organics to CH4 (based on δ 13 C-CH4 and δ 13 C-CO2 values). Wells with SO4 2− concentrations from 2 to 10 mM had bacterial populations dominated by several different sulfate-reducing bacteria and archaea that were mostly novel and unclassified. In contrast, in wells with SO4 2− concentrations <1 mM, the sequences were dominated by presumptive syntrophic bacteria as well as archaeal Methanosarcinales and Methanomicrobiales . The presence of sequences indicative of these bacteria in low SO4 2− methanogenic wells may suggest a syntrophic role in coal biodegradation and/or the generation of methanogenic substrates from intermediate organic compounds. Archaeal sequences were observed in all sampled zones, with an enrichment of sequences indicative of methanogens in low SO4 2− zones and unclassified sequences in high SO4 2− zones. However, sequences indicative of Methanomassiliicoccales were enriched in intermediate SO4 2− zones and suggest tolerance to SO4 2− and/or alternative metabolisms in the presence of SO4 2− . Moreover, sequences indicative of methylotrophic methanogens were more prevalent in an intermediate SO4 2− and CH4 well and results suggest an important role for methylotrophic methanogens in critical zone transitions. The presented results demonstrate in situ changes in bacterial and archaeal population distributions along a SO4 2− gradient associated with recalcitrant, organic carbon that is biodegraded and converted to CO2 and/or CH4 .